On the Continuity Between Art and Play: Mimesis and Fiction Between Gombrich and Walton (Itinera, 2024)
Mimesis is a key concept in the debate that led to the dawn of analytic aesthetics, namely that of the ontology of art. In particular, Kendall Walton's reading of mimesis follows Ernst Gombrich's insights, and it radicalizes the line of continuity between art and play. Walton identifies a cross–cutting form of representationality which is common to many practices, such as play, art, and sports. The purpose of this essay is to highlight the divergences between Walton and Gombrich on the object of representation. Besides, the aim of the paper is also to investigate whether Walton's claim that representationality in games and artworks is identical and not merely analogous may underlie artistic practice.
Keywords: Make–believe; Walton; Gombrich; play; mimesis; depiction